Approximate stationary densities, and parameter estimations for time-delayed stochastic logistic growth laws - Rupšys, Petras (Lietuvos matematikos rinkinys, 2007)
We consider stochastic logistic type delayed growth model (Verhulst, Gompertz, Richards) of a single species population.The objective of this paper is to deduce a procedureon the estimation of parameters. We derive approximate stationary distributions in the case of small time delays. For the estimate of parameters we apply the L1 distance procedure. We propose approximate estimations of the parameters.
Keywords: stochastic logistic growth; Fokker–Planckequation; stationary solution; parameter estimation